Investigation of Hydrogen Incorporations in Bulk Infinite-Layer Nickelates - Puphal, P.; Pomjakushin, V.; Ortiz, R. A.; Hammoud, S.; Isobe, M.; Keimer, B.; Hepting, M. (Frontiers in Physics, 2022)
Infinite-layer (IL) nickelates are an emerging class of superconductors, where the Ni1+ valence state in a square planar NiO2 coordination can only be reached via topotactic reduction of the perovskite phase. However, this topotactic soft chemistry with hydrogenous reagents is still at a stage of rapid development, and there are a number of open issues, especially considering the possibility of hydrogen incorporation. Here, we study the time dependence of the topotactic transformation of LaNiO3 to LaNiO2 for powder samples with x-ray diffraction and gas extraction techniques. While the hydrogen content of the powder increases with time, neutron diffraction shows no negative scattering of hydrogen in the LaNiO2 crystal lattice. The extra hydrogen appears to be confined to grain boundaries or secondary-phase precipitates. The average crystal structure, and possibly also the physical properties, of the primary LaNiO2 phase are, therefore, not noticeably affected by hydrogen residues created by the topotactic transformation.